Pemetaan Indeks Khusus Penanganan Stunting (IKPS) Indonesia menggunakan Metric Multidimensional Scaling (MMDS) - Purnama, Eka (Hasanuddin University, 2025)
This study aims to map the Special Handling Index for Stunting (Indeks Khusus Penanganan Stunting/IKPS) in Indonesia using Metric Multidimensional Scaling (MMDS) to identify spatial patterns and similarities in characteristics among provinces. The MMDS analysis produced a visualization that grouped 34 provinces into 10 clusters with similar IKPS characteristics and spatial proximity within each group. Additionally, three provinces were identified as outliers due to their significantly greater spatial distances from other provinces, these provinces are DI Yogyakarta, Gorontalo, and Papua. Model quality evaluation showed a STRESS value of 0.0248 and a coefficient of determination (R²) of 0.9993, indicating an excellent fit in representing the spatial data, thus making the clustering model on the spatial map reliable for use. These findings provide a comprehensive overview of the distribution and characteristics of stunting handling in Indonesia. Therefore, the clustering results can serve as a strategic foundation for stakeholders and policymakers in designing strategies and implementing more focused and effective interventions to address and manage stunting across various regions in Indonesia.